COPB2-shRNA suppresses cell growth and induces apoptosis of STAD SGC-7901 cells via inactivation of p38 MAPK/Smad2/Chk1/2 as an oncogene - Li, Hailong; Song, Yao-Hui; Du, Zheng-Ping; Zhang, Xueyan; An, Cai-Xia; Hu, Yonghua; Tian, Yihong; Wu, Zhiwei; Wu, Hongyan; Chen, Che (Translational Cancer Research, 2018)
Background: COPB2 is a subunit of the coatomer cytoplasmic protein complex that binds dilysine motifs and associates with Golgi non-clathrin-coated vesicles. At present, gradually increased reports suggested that COPB2 is overexpressed in multiple malignant tumors, however, the function and role of COPB2 in human stomach adenocarcinoma (STAD) still be kept in suspense. This study aimed to discover the significance and function of COPB2 in STAD, and to evaluate whether it could act as a potential molecular target for early diagnosis and gene therapy in STAD. Methods: COPB2 expression in STAD tissue and clinical pathological characteristics were analyzed with the aid of UALCAN and GEPIA online database. COPB2 expression between STAD cell lines and GES-1 cells was measured by real-time PCR and compared. Lentivirus COPB2-shRNA was constructed and infected into SGC-7901 cells to analysis its influences on cancerous behavior. The effects of RNAi-mediated COPB2 downregulation on SGC-7901 cell proliferation and colony-formation ability were detected by MTT and Cellomics Array Scan imaging assay detection, and colony-formation assay respectively. The effects of COPB2 downregulation on SGC-7901 apoptosis were analyzed by FCW detection, and an antibody array of stress and apoptosis signaling pathway was used to explore relevant molecular mechanisms caused by COPB2 knockdown. Results: COPB2 is upregulated in STAD tissues, and which was associated with cancer stage1, H. pylori infection and histological subtypes. COPB2 mRNA was expressed highly in STAD cell lines. Knocking down of COPB2 in SGC-7901 by COPB2-shRNA lentivirus infection significantly inhibited cell growth and colony formation ability, promoted cell apoptosis, and antibody array assay revealed that phosphorylation protein of Bad, Smad2, p38 MAPK, IkBa (Total), Chk1, Chk2 and TAK1 were down regulated significantly after COPB2 silenced in SGC-7901 cells. Conclusions: COPB2 is overexpressed in STAD tissues and cell lines compared with normal stomach tissue and cell line. Knockdown of COPB2 in SGC-7901 could inhibit cell growth and colony formation ability, promote cell apoptosis, and the mechanisms of which were associated with inactivation of phosphorylation expression of Smad2, p38 MAPK signal pathway. Therefore, it may be considered as a valuable target for gene therapeutic strategies in STAD.